SHEFEX 2 - The Vehicle, Subsystems and Mission Concept for a Hypersonic Re-entry Flight Experiment - Turner, John; Hörschgen, Marcus; Jung, Wolfgang; Turner, Peter (2007)
The first launch of the SHarp Edge Flight EXperiment (SHEFEX) was from Andøya Rocket Range (ARR) Norway, in October 2005. Its purpose was to investigate the aerodynamic behaviour and thermal problems of an unconventional shape for re-entry vehicles comprising multi-facetted surfaces with sharp edges and an asymmetric form and to provide a correlation of numerical predictions with the flight results for velocities up to the order of Mach 7. The success of the first mission has led to the approval of the SHEFEX 2 project which will involve a facetted but symmetrical fore body with a canard control system to obtain further data on the aerodynamic and thermal effects at hypersonic velocities. The canard system should provide control in all axes and predefined angles of attack of up to +/-5 degrees during the re-entry phase. The Mobile Rocket Base (MORABA) of the German Aerospace Centre (DLR) is again responsible for the vehicle, payload, service systems and test flight of the SHEFEX 2 experiment on a two-stage, solid propellant, sounding rocket.